2012
DOI: 10.1007/s12032-012-0327-4
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension as a predictive biomarker in bevacizumab treatment for colorectal cancer patients

Abstract: Bevacizumab treatment is associated with an increased risk of hypertension (HTN), a potential marker for effectiveness. We aimed to assess whether grades 2-3 HTN during bevacizumab treatment was associated with increased overall survival (OS) or progression-free survival (PFS). One hundred and eighty-one patients with metastatic colorectal cancer (CRC), who were treated in our Department from January 2009-February 2011 were included. Bevacizumab was administered jointly with standard first- or second-line chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 10 publications
4
33
1
Order By: Relevance
“…The development of Bev-induced arterial HT has recently been suggested as a potential predictive marker. Certain studies have reported that HT may predict Bev treatment efficacy, regardless of the analyzed endpoint (OS, PFS, or response rate) (17)(18)(19)(20)(21). In the present study, second-line OS tended to be longer in patients developing HT.…”
Section: Discussionsupporting
confidence: 47%
“…The development of Bev-induced arterial HT has recently been suggested as a potential predictive marker. Certain studies have reported that HT may predict Bev treatment efficacy, regardless of the analyzed endpoint (OS, PFS, or response rate) (17)(18)(19)(20)(21). In the present study, second-line OS tended to be longer in patients developing HT.…”
Section: Discussionsupporting
confidence: 47%
“…Interestingly, many clinical trials have found that patients with mCRC treated with bevacizumab who developed hypertension had a better prognosis than those without hypertension [16-22]. These results were obtained through retrospective analysis of a relatively small dataset, but the findings are statistically significant and supported by other studies [6].…”
Section: Introductionmentioning
confidence: 67%
“…Among the seven trials selected, five [16,17,19,21,22] included relevant data. The pooled analysis showed that the occurrence of hypertension induced by bevacizumab also resulted in a statistically significant improvement in OS compared with no hypertension (HR = 0.50; 95% CI: 0.37–0.68, P <0.001; heterogeneity χ 2  = 5.12, P for heterogeneity = 0.275; I 2  = 21.9%) (Figure  3).…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, according to systematic review and meta-analysis, the incidence of all grade hypertension in patients with solid tumors receiving bevacizumab was 23.6 (95% CI 20.5 --27.1) whereas the relative risk of developing high-grade hypertension was 5.28 (95% CI 4.15 --6.71) with an incidence of 7.9 (95% CI 6.1 --10.2) [45]. Interestingly multiple studies had noted that bevacizumab-induced hypertension was correlated with better oncologic response to treatment [46][47][48] and might serve as surrogate for anti-tumor efficacy of the agent [49]. Recently some genetic markers were studied to identify whether genetic variation in the VEGF pathway or in hypertension-associated genes could predict bevacizumab-induced hypertension.…”
Section: Toxicitymentioning
confidence: 99%
“…The identification of biomarkers able to predict either the efficacy or toxicity of antiangiogenic drugs is a compelling need across all cancer types and recently genetic variants for bevacizumab-induced hypertension were validated in breast cancer setting. At the same time multiple studies in colorectal and glioblastoma cancer patients suggested that hypertension induced by VEGF antibody was correlated with better treatment outcome allowing the consideration of hypertension as a predictive biomarker of clinical response [48,[80][81][82]. Bevacizumab-related toxicities, particularly hypertension and thromboembolism, need to be carefully evaluated and balanced in relationship of the peculiar characteristics of EC patients often at high risk of cardiovascular events.…”
Section: Expert Opinionmentioning
confidence: 99%